Long-term skeletal and dentoalveolar effects of hybrid rapid maxillary expansion and facemask treatment in growing skeletal Class III patients: a retrospective follow-up study - Giuliano B. Maino; Francesca Cremonini; Giovanna Maino; Emanuele Paoletto; Matteo De Maio; Giorgio Alfredo Spedicato; Mario Palone; Luca Lombardo (SpringerOpen, 2022)
Abstract Background Regardless of the treatment protocol, stability in Class III patients always represents a major concern. The aim of this study was to assess the short and long-term skeletal and dentoalveolar modifications in a group of class III patients treated with hybrid rapid maxillary expander (RME) and facemask (FM). Indeed, no long-term studies have been conducted yet with the objective of evaluating the effects of this kind of approach when applied to patients who have already gone thought their peak of growth. Material and methods 27 patients with skeletal Class III malocclusion were treated using hybrid RME according to alternating rapid maxillary expansion and constriction (ALT-RAMEC) protocol, followed by 4 months of facemask therapy. After the orthopaedic phase, each patient underwent orthodontic treatment with fixed multibracket appliances. A mean follow-up of 7 years, 10 months was performed. Pre-treatment (TO), post-treatment (T1) and follow up (T2) cephalometric tracing were analysed, comparing dental and skeletal measurements. Results Point A advanced by a mean of 3.5 mm with respect to VerT, then relapsed by 0.7 in the post-facemask period, thereby yielding of a mean advancement of 2.7 at T2. The sagittal relationship significantly changed after RME + facemask protraction (3.8° of ANB and 5.189 mm of Wits). Although both Wits and ANB values worsened over time, the improvement from T0 is still appreciable at T2. Conclusion Despite the physiological relapse due to mandibular growth, the long-term cephalometric follow-up confirms the maintenance of all positive outcomes of the previous orthopaedic treatment with hybrid RME and facemask.